Design of a Novel High Power V-Band Helix-Folded Waveguide Cascaded Traveling Wave Tube Amplifier - Tianxiang Zhuge; Yulu Hu (Active and Passive Electronic Components)
A design of a V-band Helix-Folded Waveguide (H-FWG) cascaded traveling wave tube (TWT) is presented. In this cascaded structure, a digitized nonlinear theory model is put forward first to simulate these two types of the tubes by common process. Then, an initial design principle is proposed, which can design these two different kinds of tubes universally. Using this principle, a high-gain helix TWT is carefully designed as a first stage amplifier followed by a FWG TWT to obtain high power. Simulations predict that a peak power of 800 W with saturated gain of 60 dB from 55 GHz to 60 GHz can be achieved.